Numerical and Experimental Analyses of Track Shoe Patterns for Vehicle on Sandy Terrain - Ignatius Pulung Nurprasetio; Wirya Wicaksana; Siti Zulaikah; Bentang Arief Budiman (EPI International Journal of Engineering, 2022)
A track is a vehicle propulsion system that consists of a continuous band of chains connected with track shoes or may be entirely made of rubber. The track system is still commonly used on various vehicles, including bulldozers, excavators, tanks, and tractors, and has recently been used in lunar expedition vehicles. A tracked vehicle is mainly designed to provide better mobility in rough, uneven, or slippery terrain. The main component of the track system is track shoes or so-called grousers. This track shoe geometry will determine the tractive performance of the vehicle. If an incorrect shape is used, the excavator will most likely slip. The previous study approached this traction problem by using the semi-empirical method. However, until now, the track geometry and traction relation are still unclear. This research focuses on the effects of track shoe geometry on tractive performance and vehicle climbing ability. The analysis was mainly conducted with a DEM (Discrete Element Method) simulation. The result from the experimental test is also confirmed using a small-scale RC prototype on simulated terrain with different slope variations. It is proven that the grouser height directly affects the climbing performance of tracked vehicles. A higher grouser height proves to be better at a higher inclination slope. However, for a low inclination angle, the flattened track was better. The traction result from the EDEM simulation also yields a similar result. However, higher usable traction means more friction is generated; therefore, the track with higher traction also takes more energy to cover the same distance.